Community Participation in Preparing the Village Government Working Plan - Megawati, Suci; Cahya Pratama, Andy; Hanin Sajida, Rania; Rahaju, Tjitjik (Iapa Proceedings Conference, 2024)
This study aims to determine the level of community participation in the preparation of the Village Government Work Plan (RKPDes) in Krangkong Village, Kepohbaru District, Bojonegoro Regency. This study uses a qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. This research involved the local community, village officials, and related parties in the process of preparing the RKPDes. The research focus uses eight steps of community participation according to Sherry Arnstein, namely: 1) Manipulation; 2) Therapy; 3) Provision of Information; 4) Consultation; 5) Appeasement; 6) Partnership; 7) Delegated power of attorney; and 8) Community Control. Data analysis was performed using the Miles and Huberman Data Analysis interactive model, which involved grouping and interpreting the data obtained. The results of this study indicate that community participation in the preparation of the RKPDes in Krangkong Village is still limited. Even though there are efforts from the village government to involve the community in the decision-making process, the level of participation is still low. Factors that influence community participation include the level of community awareness, limited knowledge and skills, and the active involvement of the village government in mobilizing community participation. This research recommends several steps to increase community participation in preparing the RKPDes in Krangkong Village. First, ensure that community participation in preparing the RKPDes does not stop at the planning stage. Encourage community involvement in the implementation and monitoring of projects contained in the RKPDes, so that participation becomes long-term and sustainable. Second, appreciate and recognize the community's contribution in preparing the RKPDes. Ensure that minority or marginalized groups also have equal opportunity to participate and speak out. Third, provide adequate socialization and information to the community regarding the process of preparing the RKPDes, the importance of their participation, and their role in decision making. Fourth, involve the community in the public consultation stage from the start of the RKPDes planning, and fifth, ensure that the decision-making process involves all parties related to the issues or activities to be worked on. It is hoped that this research can provide a better understanding of increasing community participation in the preparation of the RKPDes in Krangkong Village, as well as providing input for the village government and related parties in planning and implementing participatory policies at the village level.